CONSTRUCTION OF CALCULATION OF REINFORCED CONCRETE STRUCTURES FROM THE POSITION OF DESTRUCTION MECHANICS - Колчунов, В. І.; Еддін, Масуд Нур; Котенко, О. В. (Proceedings of National Aviation University (archive), 2021)
The selection of two-cantilever elements, which include a crack for reinforced concrete rods that are bent, stretched and compressed, based on the usual method of cross sections, is considered. Due to the presence of these elements, it becomes possible to find the parameters of the stress-strain state of reinforced concrete structures from the standpoint of fracture mechanics, provided that the dependence of the rate of energy release during crack formation and advancement. The calculation formulas for the realization of this dependence are given. The proposed two-cantilever elements are distributed according to the calculation of reinforced concrete elements with multi-tiered reinforcement located at an arbitrary angle to the horizontal.